2016
DOI: 10.5863/1551-6776-21.4.308
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin: Clinical Applications in Pediatrics

Abstract: As seen over the past 20 years, calprotectin has evolved as a novel, non-invasive biomarker of gastrointestinal (GI) inflammation. We present this review of calprotectin in pediatrics. This article will focus on studies using calprotectin concentrations from different body fluids to monitor inflammation in different disease states and conditions. The ultimate goal of our group is to lay down a foundation as we consider using calprotectin prospectively as a marker of intestinal inflammation that could lead to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 98 publications
0
32
0
Order By: Relevance
“…Calprotectin is a major cytosolic protein of leucocytes, especially neutrophils. Elevated levels of calprotectin are evident in infectious and inflammatory diseases and are often used as a marker of gastrointestinal inflammation [ 54 ]. The response of serum calprotectin during H. contortus infection and the experimental treatments in our present study was inconsistent with study of Váradyová et al [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calprotectin is a major cytosolic protein of leucocytes, especially neutrophils. Elevated levels of calprotectin are evident in infectious and inflammatory diseases and are often used as a marker of gastrointestinal inflammation [ 54 ]. The response of serum calprotectin during H. contortus infection and the experimental treatments in our present study was inconsistent with study of Váradyová et al [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In children, serum calprotectin is acknowledged as an inflammatory marker in various diseases including cystic fibrosis, chronic, or acute intestinal diseases, endogenous posterior uveitis, and pediatric rheumatic diseases [28]. We hypothesized that serum calprotectin would be increased in obese children with low-grade systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The Calprotectin can activate signaling cascades in several human diseases which occurs when the protein binds to its specific receptors as target proteins such as: receptor for advanced glycated end products (RAGE), heparan sulphate proteoglycan and toll like receptor (TLR4) which is the main receptor for binding to heterodimeric complex [4,5,15,16]. The Calprotectin also has the ability to regulate the accumulation of neutrophils and macrophages, cytokine production and various processes such as: leukocyte migration, differentiation of myeloid cells, cytoskeleton rearrangement and fatty acid transport [17,18]. Several studies revealed that the lipid membrane of all eukaryote cells consists of poly unsaturated fatty acids (PUFAs) including n-3 and n-6 fatty acids which they are categorized dependent upon the last carbon-carbon double bond location from the omega carbon [19].…”
Section: Introductionmentioning
confidence: 99%